A Novel Feed-Forward Controller for PMSMs - Altun, Yusuf; Gulez, Kayhan; Mumcu, Tarik Veli; Kizilkaya, M. Ozgur (IEEE, 2013)
In this study, the current tracking problem of PMSM is handled as static feed-forward controller design for Linear Parameter Varying (LPV) system. H infinity controller formulated by means of Linear Matrix inequalities (LMI) with bounded and measurable system parameters is used. Parameter-dependent Lyapunov function is preferred to achieve robust stability against inconstant parameters, throughout the control process. The LPV controller is used in two degrees of freedom (2-DOF), by jointly adding static LPV feed-forward controller on a PI feedback controller. Space vector pulse width modulation (SVPWM) is used to generate switching signals. Overall system is simulated by Matlab/Simulink Software to evaluate the validity of the method in transient and steady state response by computer simulation. Simulation results reveal that proposed method has good dynamic performance and robustness.
Keywords: Feedforward Control; PMSM Current Control; H-infinity controller; Robust control; SVPWM; Matlab; Simulink; Energy & Fuels; Engineering